Pentecostal Orthodoxy: Toward an Ecumenism of the Spirit , by Emilio Alvarez - Ketter, David (Pneuma, 2022)
"Pentecostal Orthodoxy: Toward an Ecumenism of the Spirit , by Emilio Alvarez" published on 20 Dec 2022 by Brill.